Body proportions of elite male junior rowers in relation to competition level, rowing style and boat type - Claessens, A. L.; Bourgois, J.; van Aken, K.; van der Auwera, R.; Philippaerts, R.; Thomis, M.; Vrijens, J.; Loos, R.; Lefevre, J. (Kinesiology, 2005)
The performance of elite rowers is, beside others, determined by their physical characteristics. Anthropometric data for adult rowers emphasise the importance of body mass and body size for rowing performance. Little is known concerning the importance of proportional length development. At the 1997 World Junior Rowing Championships anthropometric measurements (body mass and 6 length dimensions) were performed on 383 elite male junior rowers. Based on these measurements several proportional length dimensions were calculated. Data on boat type were obtained by questionnaire and data on competition level were based on the results obtained during the championship. The results indicate that these rowers were heavier (Mean = 82.2±7.4 kg) and taller (Mean = 187.4±5.8 cm) and had a larger sitting height (Mean=96.8±3.2 cm) and longer legs (Mean= 90.7±3.8 cm) than a reference population. Finalists had significantly larger length dimensions than non-finalists and sweep rowers had in general larger length dimensions than scullers. No differences existed when the length dimensions were expressed proportional to the stature of the rowers. It can be concluded that elite junior rowers have larger length dimensions compared to less successful rowers, but these top athletes do not differentiate from the sub-elite athletes regarding proportional length development. Differences could be observed between sweep rowers and scullers with larger length dimensions in favour of sweep rowers.